Factors Influencing the Implementation of Environmental Management Systems in Greek Industrial Estates - Vikas, Ioannis; Sdrali, Despina; Abeliotis, Konstadinos; Apostolopoulos, Constantine (Journal of Environmental Accounting and Management, 2026)
Environmental Management Systems (EMS) offer a structured framework for the improvement of the environmental performance of a company. Moreover, organized industrial estates can offer synergies among industrial companies. The aim of the research was to identify some of the factors that affect the EMS implementation by the companies and particularly to examine the relation between synergy creation and EMS adoption, which may be an indicator that the industrial estates can provide an ideal environment for the EMS implementation. The research focused on all the companies that are located in the industrial estates of Greece, apart from the firms that are purely commercial or service oriented. The data were collected during 2013, through a structured questionnaire. Selected variables from the questionnaire were used in order to build a logistic regression model. The results indicate that improved environmental performance and willingness of the companies to improve their corporate image are factors that increase the possibility for the implementation of an Environmental Management System; On the other hand, the main obstacles are the negative effect between the cost perception of the companies towards environmental actions and the costs associated with the EMS implementation.